Extraction, characterisation, optimisation and modeling of Phalerin from Phaleria Macrocarpa (Scheff.) Boerl leaves - Ismail, Nor Fariza (2014)
Phaleria macrocarpa (Scheff.) Boerl is a medicinal plant found in Malaysia and Indonesia. This plant has been used traditionally to treat various diseases. Little studies have been done to identify compound that contributes to medicinal effect. Moreover, there is lack of studies in the method to extract those valuable components from this plant. This research focuses on the leaves part of the plant. A single compound known as phalerin is targeted and extracted from the leaves. The compound is purified and identified through chemical analysis such as High Performance Liquid Chromatography, Thin Layer Chromatography, Nuclear Magnetic Resonance and Liquid Chromatogram Mass Spectroscopy. Phalerin was tested for the bioactivity study including antioxidant, anti-inflammatory and anticancer. Then the extraction process using solid-liquid extraction method was investigated on the optimum parameters; solvent, extraction temperature, solid-to-solvent ratio and particle size. Phalerin was proven having antioxidant and anti-inflammatory activity. Water was the most suitable solvent for extraction of phalerin from the leaves compared to methanol, ethanol, ethyl acetate and hexane. Water was not only safe but also extracted most of polar compounds. The optimum temperature was at 70°C as to avoid degradation of compound. The optimum solid to solvent ratio was 1:20 (g/ml) as too much solvent leads to waste of solvent and extra energy to remove excess liquid. The smallest particle size (<250 μm) was the optimum size as smaller particle provide larger surface area for mass transfer. Extraction kinetics on extraction of phalerin found that the process reach equilibrium at 120 min of extraction duration. The first order kinetics model was applied and successfully described the extraction process. From thermodynamic study, the enthalpy change (ΔH) was found to be positive (72.51 kJ/mol), indicating the extraction process of Phaleria macrocarpa leaves is endothermic. The Gibb’s free energy was found to be negative with values range from -2.75 to -9.95 kJ/mol, indicated the extraction was spontaneous at the operating temperature. This spontaneity was favored with increasing extraction temperature. Phalerin is a bioactive compound extracted from Phaleria macrocarpa leaves and having antioxidant and anti-inflammatory activities. Standardization of extract and improvement on the extraction process along with clinical study of phalerin may added new information to this study.